Attendence Management system using RFID Technology - Haryo Kusumo; Sindhu Rakasiwi; Febryantahanuji Febryantahanuji (Universitas PGRI Semarang, 2022)
Attendance management is a problem commonly faced by companies, management using a manual system still causes problems. The problem that is often faced is the difference in employee attendance data reports because they have not been well integrated. The purpose of this study was to design an employee attendance information system at PT. Kartika Utama Semarang. From the above problems, a system is needed to integrate these needs automatically and is managed entirely by a computer using an RFID system in it so that the leadership can monitor attendance and payroll in real time. The application of the author's research and development (R&D) research method in this study. This research resulted in an information system application to facilitate the management of attendance and payroll of PT. Kartika Utama Semarang